2007
DOI: 10.1111/j.1440-1681.2007.04652.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal‐regulated Kinase Pathways May Mediate the Protective Effect of Electrical Stimulation of the Paraventricular Nucleus Against Ischaemia–reperfusion Injury of the Gastric Mucosa

Abstract: 1. The aim of the present study was to elucidate the role of the extracellular signal-regulated kinase (ERK) pathway in mediating the effects of electrical stimulation of the paraventricular nucleus (PVN) on apoptosis and proliferation induced by gastric ischaemia-reperfusion injury (GI/RI). 2. To investigate the effects of electrical stimulation of the hypothalamic PVN on gastric mucosal apoptosis and proliferation in response to ischaemia-reperfusion (I/R), we used a GI/RI model by clamping the coeliac arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…According to Zhang et al (2007), the murine stomach was incised along the greater curvature and flushed with ice-cold PBS (0.1 mol/l). The index is based on a cumulative-length scale on which an individual lesion limited to the mucosal epithelium (including pinpoint erosions, ulcers, and hemorrhagic spots) is scored according to its length as follows: 1, ≤1 mm; 2, N1 mm and ≤2 mm; 3, N2 mm and ≤3 mm.…”
Section: Measurement Of Gastric Mucosal Injury Indexmentioning
confidence: 99%
“…According to Zhang et al (2007), the murine stomach was incised along the greater curvature and flushed with ice-cold PBS (0.1 mol/l). The index is based on a cumulative-length scale on which an individual lesion limited to the mucosal epithelium (including pinpoint erosions, ulcers, and hemorrhagic spots) is scored according to its length as follows: 1, ≤1 mm; 2, N1 mm and ≤2 mm; 3, N2 mm and ≤3 mm.…”
Section: Measurement Of Gastric Mucosal Injury Indexmentioning
confidence: 99%
“…Electrical and chemical stimulation of the PVN can obviously aggravate the SGMI, but markedly attenuate GI-RI (Zhang and Zheng, 1997;Zhang et al, 2002;Zhang et al, 2007). Meanwhile, it also has been founded that the electrical and chemical stimulation of LHA can aggravate GI-RI .…”
Section: Introductionmentioning
confidence: 96%
“…27 Because Ang II is a stress hormone, stress increases the expression of AT1 receptors in the parvocellular PVN, 28,29 and Ang II contributes to the production of stress-induced gastric ulcerations. 30 Our previous studies 10,31,32 showed that the PVN is one of the special central nervous system areas that attenuate GI-R injury. However, whether exogenous Ang II in the PVN can regulate GI-R injury is not known, nor are its possible local molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, the molecular mechanisms underlying GI-R injury are not completely understood. Our previous study demonstrated that activated ERK1/2 participates in the regulation of gastric mucosal injury and repair induced by GI-R, 9,10 but the roles of nuclear factor κB (NF-κB) in the development of GI-R injury and in the protective effects of angiotensin II (Ang II) in the paraventricular nucleus (PVN) against GI-R injury need further investigation.…”
Section: Introductionmentioning
confidence: 99%